GAME EDUKASI GRAMMAR BAHASA INGGRIS BERBASIS ANDROID DENGAN METODE COMPUTER ASSISTED LEARNING - Bahtiar Rofiq , Ardien; Nur Hakim, Fitro (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2022)
The development of technology in the current era of globalization, is quite rapid. Along with the development of technology in the education sector, several learning products and materials have been widely produced and become daily consumption for educators and learners with various versions. Educational games are one of the learning support media used to help students in learning English material, especially in passive voice materials in a fun way. This research aims to create a valid educational game applications with the application of android-based interactive quizzes for class XII MA NU Al Hikmah. The concept chosen as an educational game is to provide missions that must be completed in the game, design the difficulty of each level in the game, provide material explanations about passive voice, the differences in grammar, and evaluations in the form of passive voice questions. This research uses research and development methods or Research and Development, using 6 out of 10 research stages. Data collection is done using observations, interviews and questionnaires. The software used in this study is CorelDRAW, Adobe Audition, After Effect, Adobe Premiere, and Unity 3D.